Pulmonary Tuberculosis Outbreak among Healthcare Workers in Vachira Phuket Hospital - ยอแสงรัตน์ วีรวัฒน์ (Disease Control Journal, 2018)
The increasing incidence of pulmonary tuberculosis among the healthcare workers in Vachira Phuket Hospital was noticed. The purpose of this study was to verify the outbreak of tuberculosis among healthcare workers (HCWs) at a tertiary care, public hospital in Phuket, Vachira Phuket Hospital. The data of HCWs diagnosed with TB were collected from medical records, chest films and laboratory findings. The incidence and relative risk (RR) of tuberculosis among HCWs during 2000 and 2005 were analysed and evaluated retrospectively, then comparing to TB incidence in the general population of Thailand. In this study there were 13 HCWs with tuberculosis (5 men and 8 women). There was one doctor, 9 nurses and 3 paramedics, out of an averaged of 1,233 workers per year over the study period. The incidence of TB among the general population of Thailand was 48.37 of 100,000 persons. The incidence of tuberculosis in all HCWs of the hospital was 1054.34 of 100,000 persons (RR 21.79), 81.1 of 100,000 persons in doctor (RR 1.68), 729.97 of 100,000 persons in nurses (RR 15.1) and 243.31 of 100,000 persons in paramedics (RR 5.03 ). In conclusion HCWs in Vachira Phuket Hospital have higher risk for being sick with tuberculosis than general population, especially among the nurses.